2012
DOI: 10.1016/j.ijsu.2012.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal gastrointestinal stromal tumors: Review on clinical and surgical aspects

Abstract: Duodenal GISTs have uncertain malignant potential, and they may be asymptomatic, or present with abdominal pain or bleeding. A preoperative diagnosis can be difficult to obtain. Endoscopic ultrasound and fine needle aspiration cytology (FNAC) may be helpful. Surgical R0 resection remains the only curative approach. However, owing to the complex anatomy of the duodenum, limited resection is not always feasible. In these cases, extensive procedures such as pancreaticoduodenectomy or pancreas-preserving duodenect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
11

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 25 publications
1
12
0
11
Order By: Relevance
“…Furthermore, the median size of duodenal GISTs in our series was 4.7 cm. Similarly, most authors report a smaller size of tumor (4.0 to 5.0 cm) for duodenal GISTs compared with gastric and small bowel GISTs [6,8,11]. Interestingly, we noted that patients who ultimately required PD were more likely to present with a larger tumor and more commonly presented with a tumor in the second portion of the duodenum compared with LR.…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, the median size of duodenal GISTs in our series was 4.7 cm. Similarly, most authors report a smaller size of tumor (4.0 to 5.0 cm) for duodenal GISTs compared with gastric and small bowel GISTs [6,8,11]. Interestingly, we noted that patients who ultimately required PD were more likely to present with a larger tumor and more commonly presented with a tumor in the second portion of the duodenum compared with LR.…”
Section: Discussionsupporting
confidence: 62%
“…11, 2527 Achieving wide margins in the duodenum is not always possible; margins of fewer than 5 mm after resection of duodenal tumors are not uncommon. 9 We found that only 84% of LR were R0 resections versus 100% in the pancreaticoduodenectomy group.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of GISTs (gastrointestinal stromal tumours) possess mutually exclusive mutations in platelet‐derived growth factor subunit A (PDGFRA) or KIT, which constitutively activate the encoded receptor tyrosine kinases (RTKs) to control the response to imatinib treatment and lead to tumorigenesis . In adults, 10%‐15% of GISTs exhibit wild‐type KIT and PDGFA genes but may bear mutated neurofibromatosis type 1 (NF1), BRAF, or succinate dehydrogenase (SDH) genes .…”
Section: Introductionmentioning
confidence: 99%